Penentuan Alternatif Lokasi Ibukota Kabupaten Mojokerto Berdasarkan Stakeholder - Pratama, Iman Tunas; Zauhar, Soesilo; Rozikin, Mochamad (Fakultas Teknik, Universitas Brawijaya, 2018)
Structuring the region through good governance is the mission of every region. Based on Law Number 23 Year 2014 and Permendagri Number 30 Year 2012, he decision is made that there is a need to move the Capital of Mojokerto Regency which is currently located in Mojokerto City and set forth in the Regional Spatial Plan (RTRW) of Mojokerto Regency. This research aims to identify priority criteria in determining the location of the capital and determine the location selected based on the criteria of the capital of Mojokerto regency. The analysis used is Analytical Hierarchy Process (AHP) using Expert Choice by selecting 8 experts to conduct assessment on criteria and alternative location of capital of Mojokerto regency. The analysis result is the priority of criteria are land availability (1), accessibility (2), availability of infrastructure (3), physical condition (4), politics and security (5), policy (6), population (7), geographical (8) and historical (9). While the alternative Capital location of Mojokerto Regency that considered from the order of 9 criterion in sequence is Mojosari district (1), Sooko district (2), Trowulan District (3), Jetis district (4) and Bangsal district (5)Keywords: alternative location, stakeholder, capital regency